2013
DOI: 10.1136/jech-2013-203128
|View full text |Cite
|
Sign up to set email alerts
|

Academics and competing interests in H1N1 influenza media reporting

Abstract: BackgroundConcerns have been raised over competing interests (CoI) among academics during the 2009 to 2010 A/H1N1 pandemic. Media reporting can influence public anxiety and demand for pharmaceutical products. We assessed CoI of academics providing media commentary during the early stages of the pandemic.MethodsWe performed a retrospective content analysis of UK newspaper articles on A/H1N1 influenza, examining quoted sources. We noted when academics made a risk assessment of the pandemic and compared this with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Debate about the vaccine is difficult when respected physicians state that the vaccine works without declaring their industry funding. 30 We risk losing public trust and supporting baseless anti-vaccination sentiment by allowing drug manufacturers or For personal use only: See rights and reprints http://www.bmj.com/permissions Subscribe: http://www.bmj.com/subscribe people with close links to industry to be involved in decision making and lobbying. 6 The expert committee that advised the UK government about Bexsero could not participate in a public conversation at the time because its advice had to be approved before release.…”
Section: Competing Interestsmentioning
confidence: 99%
“…Debate about the vaccine is difficult when respected physicians state that the vaccine works without declaring their industry funding. 30 We risk losing public trust and supporting baseless anti-vaccination sentiment by allowing drug manufacturers or For personal use only: See rights and reprints http://www.bmj.com/permissions Subscribe: http://www.bmj.com/subscribe people with close links to industry to be involved in decision making and lobbying. 6 The expert committee that advised the UK government about Bexsero could not participate in a public conversation at the time because its advice had to be approved before release.…”
Section: Competing Interestsmentioning
confidence: 99%
“…In research ethics, the term "funding bias" refers to how "private funding can bias the outcome of studies toward the interests of the sponsors" (Krimsky 2003: 146). Such funding bias can be found in areas of research as diverse as criminology (Geis et al 1999), food (Massougbodji et al 2014), medicine (Davidson 1986), public health (Mandeville et al 2013), and marine mammal research (Wade et al 2010). These studies have all documented how, through statistical analysis of funding seen in relation to outcome, one can detect clear patterns that indicate that the source of the funding had aggregated effects on the outcome of the studies.…”
Section: Conflict Of Interest and Funding Biasmentioning
confidence: 99%
“…A 2007 study showed that very few newspaper stories about scientific research report the financial ties of researchers and quoted sources, even when the conflicts of interest are disclosed in the journal article [ 8 ]. In 2013, Mandeville et al [ 28 ] found that 3 of 425 newspaper articles on the 2009 to 2010 A/H1N1 pandemic noted the competing interests of the quoted researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The impact on vaccine decision-making persists even a decade later, with surveys showing that more than one in five people believe that vaccines cause autism [ 89 ]. Neuraminidase inhibitors Academics who were interviewed in newspaper articles covering the 2009 H1N1 pandemic were more likely to overestimate the risk of the pandemic or promote the use of neuraminidase inhibitors if they had conflicts of interest [ 28 ]. Only 3 of 425 newspaper articles noted the academics’ conflicts of interest.…”
Section: Introductionmentioning
confidence: 99%